THE STUDENTS’ ABILITY IN USING ENGLISH INTONATION AT THE FOURTH SEMESTER STUDENTS OF ENGLISH EDUCATION DEPARTMENT LANCANG KUNING UNIVERSITY IN ACADEMIC YEAR 2013-2014 - Syahdan Syahdan (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2014)
The phenomenon found from this research was the students did not know how topronounce appropriate intonation in speaking context because they did not realize thefunction of intonation that different intonation have different meaning. The purpose of theresearch was found out the students' ability In Using English Intonation at the FourthSemester Students of English Education Department Lancang Kuning University inAcademic Year 2013-2014. Type of the research was cross-sectional survey design aiming tobe an evaluation program. The sample of this research consisted of 27 students. Theinstrument used in this research was test. In collecting data, the researcher tested them dealtwith sentences or expression of simple patterns of English intonation namely falling andrising intonation. The data gained was analyzed by using descriptive statistics.Moreover, thefinding of the research showed that total of students’ score was 2110, the mean score was 78,mode of the students’ score was 70, median of students’ score was 75, variance of thestudents’ score was 57.33 and standard deviation of the students’ score was 7.57. The rangescore from lowest score 70 to highest score 95 was 25 points. After analyzing the data, thevariety of data was categorized into homogenous and the range of score was categorized intolow score or could be said that the mean score was representative. Then mean score ofstudents was categorized into good level based on grade course of phonology, score 70-79was categorized into good level or got score B. Inbrief, the students’ ability in using Englishintonation (simple patterns of English intonation) was categorized into “Good level”.Therefore, the findings of this research would be useful for the Phonology’s lecturer asevaluated in teaching program.